2019
DOI: 10.1002/jwmg.21801
|View full text |Cite
|
Sign up to set email alerts
|

Wildlife Interactions within Highway Underpasses

Abstract: Highway underpasses are a common management tool used to lessen wildlife‐vehicle collisions on roadways. Despite their widespread use, the effects of predator‐prey interactions and human disturbances on wildlife within underpasses have not been well studied. To understand the effect of species interactions and human disturbances on wildlife traveling through underpasses, we analyzed camera data from 3 underpasses in Hallelujah Junction Wildlife Area, Sierra County, California, USA, from June 2017 to December 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 33 publications
3
18
1
Order By: Relevance
“…The most notable of our conclusions is that predators and prey do not use wildlife passages independently and that observed dependencies seem related to size(prey)-matching, with potential repercussions for the usefulness of such structures, as was also recently pointed out by Caldwell and Klip [19]. On the one hand, crossing structures may become prey traps if predators use them to seek prey [16].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The most notable of our conclusions is that predators and prey do not use wildlife passages independently and that observed dependencies seem related to size(prey)-matching, with potential repercussions for the usefulness of such structures, as was also recently pointed out by Caldwell and Klip [19]. On the one hand, crossing structures may become prey traps if predators use them to seek prey [16].…”
Section: Discussionsupporting
confidence: 72%
“…Dickson and colleagues [17] found no evidence of cougars being attracted to crossing structures to hunt deer, and Ford and Clevenger [18] have shown that evidence of predator-prey interactions among large mammals at wildlife crossings do not match the prey-trap hypothesis in the Trans-Canada Highway. However, recently, Caldwell and Klip [19] have found that predator-prey interactions influenced underpass uses by several species, but little is known about the generality of these findings and, particularly, if passages may influence interactions between smaller-sized predators and prey. Among them, a close association between both groups may happen, and some species may show less aversion to the road environment [18].…”
Section: Introductionmentioning
confidence: 99%
“…An alternative to our conclusion that prey avoid a prey-trap (whether or not it was through temporal clustering by prey) is that predators track prey, but we failed to detect those efforts. A recent study inferred spatiotemporal avoidance from a significantly smaller sample size than seen here, while still not documenting interspecific interactions in the wildlife passages 23 . While we cannot rule out the possibility that the use of the wildlife passages here was still too infrequent for scent trails to be readily used in this study system this possibility is unlikely, especially given this earlier study.…”
Section: Discussioncontrasting
confidence: 64%
“…Only a handful of studies have empirically tested the prey-trap hypothesis in the context of wildlife passages 17 , 19 , 23 , 24 , but these offer insufficient evidence to determine the generality of a prey-trap effect 18 , 25 . In the context of wildlife passages, a prey-trap could occur via several mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce WVCs and improve migration corridors across roadways, crossing structures (i.e., underpasses and overpasses) are an effective solution in many countries (Clevenger and Waltho 2000, Olsson et al 2008, Smith et al 2015, Sawyer et al 2016 b , Caldwell and Klip 2020). Researchers have reported that wildlife crossing structures are effective at reducing mortalities and improving permeability along wildlife corridors, particularly for large migratory species, such as mule deer ( Odocoileus hemionus ; Mata et al 2008, Sawyer et al 2012, Stewart 2015, Simpson et al 2016).…”
mentioning
confidence: 99%